Compatibility Test of ALFAROL® Powder with Other Powders and Granules - TAMURA, TAKAHIRO; ITOH, MASAO; YAMAZAKI, YUKO; YOSHIMURA, TOMOKO; NISHIMURA, NAOKO; ISHIKURA, CHIYOJI; SAMIZO, KAZUO; HORIGUCHI, MASAMI (Japanese Journal of Hospital Pharmacy, 1998)
The compatibility test was conducted between alfacalcidol powder (Alfarol®powder) and other drugs which were frequent, used with alfacalcidol powder as combination drugs at dispensing, such as lactose (LA), precipitated calcium carbonate powder (CO), calcium lactate powder (CL), Calcicol®powder (CG), Ulcerlmin®finegranule (UL), Marzulene-S®granule (MS), magnesium oxide fine granule (MO), Tagamet®fine granule (TA).Gasterpowder (GA), Kolantyl granule (KO), Acenalin fine granule (AS), Temelin®grannle (TN), Rizegranule (RZ), Loxionin®fine granule (LO), Solantal®finegranule (SO), Alnert®granule (AL), and Panaldine®fine granule (PA). Combination drugs were stored at 5°C and 25°C with 75% RH. A change in the drug appearance was observed just after, and 2, 4, and 8 weeks after dispensing. In addition, the contents of alfacalcidol were also determined using high-performance liquid chromatography at the same time points. In the assessment of change in appearance, TN and LO turned to yellow 4 and 8 weeks after dispensing under the conditions at 25°C with 75% RH, respectively, however, no change was observed in the appearance in other combinations under the above two conditions. The residual rate of the alfacalcidol content declined by about to 90% or was lower at 8 weeks after dispensing in combination with GA when stored at 5°C. Under the conditions at 25°C with 75% RH, the residual rates declined by about to 90% or lower at 2 weeks after dispensing in combination with CO, UL, TA, GA, RZ, 4 weeks after dispensing in combination with KO, LO, and SO, and 8 weeks after dispensing in combination with MO and AS. The residual rates remained 90% or higher even 8 weeks after dispensing in combination with LA, CL, CG, MS, AL, and PA.